Politics of the Russian empire in relation to the Tatar population of North Caucasus in the second half of ХVІІІ of item - Bilyi, Dmytro; Futulujchuk, Vasyl (Skhid, 2016)
At the beginning ХХІ of century Ukraine again ran into imperial ambitions of Russian Federation, that resulted in a military collision and occupation of part of territory of our state. For successful opposition with the newest colonial expansion it is necessary to appeal to historical experience and analysis of basic strategies and methods of colonial Russian politics. The special personal interest causes the politician of the Russian empire in relation to the Tatar population in fact Crimea again found oneself under control Russia, and in that Tatars fold a native population. One of not popular episodes of long duration expansionist politics of the Russian empire there is her politics in relation to ногайських Tatars that inhabited North Caucasus. In the article basic directions of colonialist politics of the Russian empire are examined in relation to the Tatar population of North Caucasus during expansion in Crimea and on Caucasus the circumstances of elimination of ногайских Tatars that lived on Kuban, genocide in relation to the habitants of this territory, basic strategies, that combined for itself подрыв unities of the Tatar association, exasperating enmity between the Tatar clans and direct elimination of Tatars by direct military aggression, Are illuminated in the second half of ХVІІІ of item.